Myelocytomatosis‐Protein Arginine N‐Methyltransferase 5 Axis Defines the Tumorigenesis and Immune Response in Hepatocellular Carcinoma. Issue 4 (13th July 2021) - Luo, Yuhong; Gao, Yuqing; Liu, Weiwei; Yang, Yuan; Jiang, Jie; Wang, Ying; Tang, Wei; Yang, Shoumei; Sun, Lulu; Cai, Jie; Guo, Xiaozhen; Takahashi, Shogo; et al.
Abstract : Background and Aims: HCC is a leading cause of cancer‐related deaths globally with poor outcome and limited therapeutic options. Although the myelocytomatosis ( MYC ) oncogene is frequently dysregulated in HCC, it is thought to be undruggable. Thus, the current study aimed to identify the critical downstream metabolic network of MYC and develop therapies for MYC‐driven HCC. Approach and Results: Liver cancer was induced in mice with hepatocyte‐specific disruption of Myc and control mice by administration of diethylnitrosamine. Liquid chromatography coupled with mass spectrometry‐based metabolomic analyses revealed that urinary dimethylarginine, especially symmetric dimethylarginine (SDMA), was increased in the HCC mouse model in an MYC‐dependent manner. Analyses of human samples demonstrated a similar induction of SDMA in the urines from patients with HCC. Mechanistically, Prmt5, encoding protein arginine N‐methyltransferase 5, which catalyzes SDMA formation from arginine, was highly induced in HCC and identified as a direct MYC target gene. Moreover, GSK3326595, a PRMT5 inhibitor, suppressed the growth of liver tumors in human MYC‐overexpressing transgenic mice that spontaneously develop HCC. Inhibition of PRMT5 exhibited antiproliferative activity through up‐regulation of the tumor suppressor gene Cdkn1b /p27, encoding cyclin‐dependent kinase inhibitor 1B. In addition, GSK3326595 induced lymphocyte infiltration and major histocompatibility complex class II expression, which might contribute to the enhanced antitumor immune response. Combination of GSK3326595 with anti–programed cell death protein 1 (PD‐1) immune checkpoint therapy (ICT) improved therapeutic efficacy in HCC. Conclusions: This study reveals that PRMT5 is an epigenetic executer of MYC, leading to repression of the transcriptional regulation of downstream genes that promote hepatocellular carcinogenesis, highlights a mechanism‐based therapeutic strategy for MYC‐driven HCC by PRMT5 inhibition through synergistically suppressed proliferation and enhanced antitumor immunity, and finally provides an opportunity to mitigate the resistance of "immune‐cold" tumor to ICT.